New aryloxy-quinone derivatives as potential anti-Chagasic agents: synthesis, trypanosomicidal activity, electrochemical properties, pharmacophore elucidation and 3D-QSAR analysis1. Issue 80 (2nd September 2015) - Vázquez, Karina; Espinosa-Bustos, Christian; Soto-Delgado, Jorge; Tapia, Ricardo A.; Varela, Javier; Birriel, Estefanía; Segura, Rodrigo; Pizarro, Jaime; Cerecetto, Hugo; González, Mercedes; Paulino, Margot; Salas, Cristian O.
<x xml:space="preserve">Abstract</x> A set of new aryloxy-quinones were synthesized and evaluated in vitro against the epimastigote form of Trypanosoma cruzi and their unspecific cytotoxicity was tested on murine macrophages J-774 cells.